A study on the effect of dilutions and buybacks on the pricing of equity and stock based claims using a finite difference mesh - Boynton, Matthew (Department of Finance and Tax, 2023)
We study a model of the firm, with perpetual debt and a continuously payable coupon as well as the possibility to raise cash via equity issuance. Excess cash is paid back to shareholders either via dividends or via buybacks. The number of shares changes when equity is issued and when the firm buys back shares. Using this model we track the total number of shares in issue. Then we use finite difference methods to investigate the differences in pricing options on a fixed portion of equity and options linked to the share price, as well as implications for American options on equity.